2021
DOI: 10.1002/jgc4.1379
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling for early onset and familial dementia: Patient perspectives on exome sequencing

Abstract: Dementing illnesses are progressive, neurodegenerative conditions most commonly occurring sporadically after age 65. A subset of dementia cases, however, are hereditary (Bekris et al., 2010) and have been shown to be caused by pathogenic variants in genes such as PSEN1, PSEN2, APP, GRN, and MAPT (Blue et al., 2018) and by C9orf72 GGGGCC hexanucleotide repeat expansions (Lee et al., 2014). Still, many familial cases remain unsolved by genetic testing and are not sufficiently explained by known risk alleles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…The positive correlation between factor 2 and factor 3 ("Perceived Benefits of Testing") is in line with the previous validation study of Angelidou et al (2023), who also found a comparable correlation between their second ("Intention to be Screened") and third factor ("Preventive Health Behaviors"). The relationship between both constructs is underlined by other studies, as the majority of the mentioned benefits are the most convincing motivations for pursuing pre-symptomatic screening (Chao et al, 2008;Wikler et al, 2013;Rolf et al, 2021). Conversely, factor 1, "Perceived Harms of Testing", exhibits weak negative correlations with the other factors.…”
Section: Psychometric Properties 25-item Pre-adsmentioning
confidence: 87%
“…The positive correlation between factor 2 and factor 3 ("Perceived Benefits of Testing") is in line with the previous validation study of Angelidou et al (2023), who also found a comparable correlation between their second ("Intention to be Screened") and third factor ("Preventive Health Behaviors"). The relationship between both constructs is underlined by other studies, as the majority of the mentioned benefits are the most convincing motivations for pursuing pre-symptomatic screening (Chao et al, 2008;Wikler et al, 2013;Rolf et al, 2021). Conversely, factor 1, "Perceived Harms of Testing", exhibits weak negative correlations with the other factors.…”
Section: Psychometric Properties 25-item Pre-adsmentioning
confidence: 87%
“…When individuals who are suspected of carrying an AD gene have tested negative on a focused panel of established dementia genes (such as the three AD genes as well as frontotemporal dementia-associated genes [MAPT, GRN, TBK1, C9orf72] and PRNP, which causes prion disease), little appears to be gained from proceeding to expansive exome sequencing. 101,102 Therefore, although exome sequencing has been pursued on a large-scale research basis, it remains of limited use in the clinic.…”
Section: Genetic Testingmentioning
confidence: 99%
“…As discussed above, however, families with mendelian forms are rare. Once high-throughput sequencing facilitated genetic testing in well-phenotyped research cohorts, it became apparent that even in patients with an age of onset younger than 65 years, the rate of carrying a pathogenic variant in an established AD gene is low, estimated at between 1% and 6% 8,101,102 . In the author’s clinic, for individuals with a family history of early-onset AD and for those with an early onset (younger than age 55) even without a family history of AD, a discussion regarding genetic testing for APP, PSEN1 and PSEN2 is typically initiated if patients have not raised the question themselves.…”
Section: Genetic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, genetic counseling – which encompasses counseling and support in addition to the information provision that was provided in these studies – has been hypothesized to be an effective strategy to elicit meaningful behavior change to reduce the risk for common complex diseases [12]. For example, studies of providing genetic risk information in the context of genetic counseling about Alzheimer’s disease have found some evidence to suggest that it may influence diet and exercise habits for some individuals [20].…”
Section: Introductionmentioning
confidence: 99%